Comparative Study of Prolene Hernia System and Lichtenstein Method for Open Inguinal Hernia Repair - Badkur, Mayank (J Clin Diagn Res, 2015)
BACKGROUND: Prolene Hernia System (PHS) is a bi-layered polypropylene mesh with a connector that combines the anterior and posterior inguinal hernia repair, but still not very popular in this part of the country. Hence a prospective & randomized comparative study was undertaken to compare PHS with the already popular Lichtenstein Hernia Repair (LHR) and determine the post-operative outcome. MATERIALS AND METHODS: Total 67 inguinal hernia repairs were randomly assigned to either PHS or LHR method, and data was collected regarding various outcome measures like duration of surgery, post-operative pain, requirement of analgesia, return to normal activity, and early and late complications. RESULTS: Mean duration of surgery was significantly higher for PHS group than LHR group (65.4 min vs 51.26 min, p-value <0.0001). Significant difference was noted between the PHS and LHR group in terms of moderate to severe post-operative pain (15.15% vs 41.18%,p-value 0.018), time of requirement of analgesia (3.7 vs 4.6 days, p-value 0.024), and time to return to normal activity (2.7 vs 3.4 days, p-value 0.023), all in favour of the former technique. No intra-operative complication was noted in either of the groups. 5 patients had early complications in PHS group and 6 in LHR group, but this was statistically not significant. The average time of follow-up for the study was 7.8 month, ranging from 1 to 18 months. Chronic inguinal pain was noted in 1 and 2 patients respectively in PHS and LHR group, again statistically not significant. No recurrence was noted in both the groups till the time of follow-up. CONCLUSION: PHS is a safe and better alternative to the time honored Lichtenstein hernia repair with the added advantage of strengthening whole of myopectineal orifice, and virtually eliminating any risk of recurrence.